Leveraging and risk taking within the German banking system: Evidence from the financial crisis in 2007 and 2008 - Frank Schmielewski (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2012)
The present study is centered primarily on determining whether the German banking system is to be characterized by procyclical behavior from 2000 to 2011 and to what extent specific sectors of the German banking system showed significant balance sheet operations to increase their leverage within years of booming asset prices. First, the results of this study show that the different sectors of the German banking system operate their business more or less procyclically. Second, the study provides some empirical evidence that banks increasing their leverages during periods of extraordinary high returns provided in the financial markets preferred funding their assets by shortterm lending in the interbank market. Third, the study clarified that banks, preferring high leverages, can apparently be characterized by a high volatility of return on assets and low distances to default over the observation period. Finally, the examined regression models provide some empirical evidence that requirements on countercyclical capital buffers should be considered by regulatory authorities in the context of macroeconomic indicators.
Keywords: G01; G12; G14; G28; G15; G32; 330; liquidity and leverage; financial crises; asset pricing; information and market efficiency; government policy and regulation; international financial markets; funding policy; financial risk and risk management; capital and ownership structure; countercyclical capital buffers; distance to default; Bank; Kapitalstruktur; Bankenliquidität; Konjunktur; Finanzmarktkrise; Eigenkapitalvorschriften; Deutschland